11=-4(4m-5)+2(m+5)

Simple and best practice solution for 11=-4(4m-5)+2(m+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11=-4(4m-5)+2(m+5) equation:


Simplifying
11 = -4(4m + -5) + 2(m + 5)

Reorder the terms:
11 = -4(-5 + 4m) + 2(m + 5)
11 = (-5 * -4 + 4m * -4) + 2(m + 5)
11 = (20 + -16m) + 2(m + 5)

Reorder the terms:
11 = 20 + -16m + 2(5 + m)
11 = 20 + -16m + (5 * 2 + m * 2)
11 = 20 + -16m + (10 + 2m)

Reorder the terms:
11 = 20 + 10 + -16m + 2m

Combine like terms: 20 + 10 = 30
11 = 30 + -16m + 2m

Combine like terms: -16m + 2m = -14m
11 = 30 + -14m

Solving
11 = 30 + -14m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '14m' to each side of the equation.
11 + 14m = 30 + -14m + 14m

Combine like terms: -14m + 14m = 0
11 + 14m = 30 + 0
11 + 14m = 30

Add '-11' to each side of the equation.
11 + -11 + 14m = 30 + -11

Combine like terms: 11 + -11 = 0
0 + 14m = 30 + -11
14m = 30 + -11

Combine like terms: 30 + -11 = 19
14m = 19

Divide each side by '14'.
m = 1.357142857

Simplifying
m = 1.357142857

See similar equations:

| 5*-17=-x+7 | | (7k-3)(k-2k+7)= | | 5(5p+6)+5(1-3p)=75 | | (21a+5)-(4a+13)=11 | | 8u-24= | | -14=-3(2+4n)+4(-2n-2) | | -31-7x=-2(x-2) | | -6(-a+4)=3a-30 | | p=223x | | 3(-n+2)-1=-3n+5 | | -32-7=-3(-8+7v) | | 2n+7=11 | | 2k-(k-1)=7 | | 1+5p= | | -4+5(k-2)=7k-8 | | 15x+187=3x | | -2a+14b=6c | | 8k-(4k-1)=28 | | -6x+6(5+x)=-8x-26 | | -r=6-8(r+6) | | -7-5(1-8x)=-212 | | Y/3-11=16 | | 5-x=3.5 | | -7(1+8n)=385 | | 2h-(h-1)=9 | | 5v+8=63 | | x(x^3-x^2-3x+1)+2=0 | | x^4-x^3-3x^2+x=0 | | x^4-x^3-3x^2+x+2=0 | | 150=-3(-8-6r) | | x^4-x^3-3x^2+x^1+2=0 | | U/5-16=26 |

Equations solver categories